ANALISIS KESTABILAN LERENG MENGGUNAKAN METODE BISHOP PADA JALAN UTAMA MENUJU PENAMBANGAN DI PT. CAHAYA BUMI PERDANA, KOTA SAWAH LUNTO - Satria Al Rafid; Yoszi Mingsi Anaperta (Departemen Teknik Pertambangan FT UNP, 2021)
Abstract. PT. Cahaya Bumi Perdana is a company engaged in the coal mining business in Sawahlunto City. Mining activities carried out are open pit mining system with replenishment method and underground mining system using space and pillar method. In August 2020 there was a landslide on the main road to the mining site. The type of slope forming material is clay. The assumed arc landslide stretch with the initial slope geometry before the landslide is 70 ° and 35 meters high. Landslides disrupt the main road access to the mine due to falling material. The method used in this research is the bishop method and the hoek and bray method. The results of this study can be ignored as follows. Data from laboratory testers were density 9,212 kN/m3 , cohesion 53,462 kN/m2 , and deep shear 22,950. The density value in dry conditions is 8,065 kN / m3, and at saturated conditions is 10,196 kN/m3 . The slope factor in natural conditions is 1.267, 1.372 in dry conditions, and 1.178 in saturated conditions. Recommended slope geometry using the bishop method with a new slope height of 17 meters, a width of 10 meters and a slope of 500 per level, and 420 for the total slope, obtained a new safety factor. The total safety factor in dry conditions is 2,223 and single slop is 3,031. In saturated conditions, the total is 1,932 and 2,546 singles. With the hoek method, the safety factor for new slopes in dry conditions is 2.49 and 1.93 in saturated conditions with the same height, width and slope as the bishop method.Key Words : Safety Factor, Bishop Metode, Slope.